Pelaksanaan Pengadaan Pasokan Bahan Baku Karkas Ayam: Studi Kasus pada Rumah Makan “Ayam Bakar Wong Solo” Jember - Zahro, Fatimatuz; Poernomo, Djoko; Iswono, Sugeng (University of Jember, 2016)
Abstract This research aimed to determine and describe the implementation of supply procurement of chicken carcass as the raw materials at “Ayam Bakar Wong Solo” Restaurant Jember that causes delays and unfulfillment of the quantity of chicken carcass ordered. The research used qualitative paradigm with case study design. Data were collected by in-depth interview, passive observation, and documentation. Data analysis used analyses of domain, taxonomy, and fishbone diagram. The result showed that